Memanfaatkan Kearifan Lokal dan Keunikan Budaya Bena Melalui Promosi Video Drone Berbasis Web Untuk Meningkatkan Ekonomi Masyarakat - Oka, Gde Putu Arya; Pare, Prisko Yanuaris Djawari; Prayoga, I Gede Putu Adithya (IMEDTECH (Instructional Media Design and Technology) e-ISNN 2580-6033, 2024)
Abstract Bena Village is one of the traditional villages located in Tiworiwu Village, Jerebuu District, Ngada Regency, Flores, East Nusa Tenggara. In the Jerebuu area, there are many traditional villages with original megalithic heritage as a milestone for the arrival of several tribes to Ngada Regency. Each tribe has its own uniqueness, culture and archaeological heritage. What is the same in several traditional villages is; (1) the arrangement of residential space patterns where traditional houses surround an open space. Inside there are Ngadgu and Bagha as symbols of ancestors. (2) the form of the building known as SA'O, (3) and traditional rituals such as Reba. The differences are seen in terms of (1) accessories used in traditional buildings, the activities of village residents, arts and crafts and artifacts produced. The existence of the traditional village is still preserved even though some of its ornaments and cosmetics have changed due to the difficulty of finding natural materials and the development of the times. The outside world has known the Bena traditional village through several posts on social media or verbal communication by word of mouth after visiting Bena. There is no promotional media that can be said to be officially managed directly by the management group. In addition, the management group has not been touched by activities to increase the capacity of managers. Therefore, this service is to create web-based promotional media and hold training to strengthen HR capacity, especially promotional strategies and TOT related to the operation of promotional media